2001
DOI: 10.1093/rheumatology/40.6.652
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in Behcet's disease: a retrospective survey from a single UK centre

Abstract: In our population, BD confers a 14-fold risk of developing venous thrombosis. The risk is sixfold higher in male BD patients, who fare worse than females with regard to thrombophlebitis, folliculitis and retinal vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 8 publications
0
50
0
1
Order By: Relevance
“…Risk factors for thrombosis were identified like Factor V Leiden (FVL), Anti B2 glycoprotein 1 antibodies, Anti cardiolipin Antibodies, Lupus anticoagulant and MTHFR mutations. FVL was identified in 30-37.5% of BD patients from Turkey and Saudi Arabia [13]. The prevalence of thrombophilia among our BD patients was high and the prevalence of Anti B2 glycoprotein 1 antibodies and Anti cardiolipin Antibodies were more than FVL.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Risk factors for thrombosis were identified like Factor V Leiden (FVL), Anti B2 glycoprotein 1 antibodies, Anti cardiolipin Antibodies, Lupus anticoagulant and MTHFR mutations. FVL was identified in 30-37.5% of BD patients from Turkey and Saudi Arabia [13]. The prevalence of thrombophilia among our BD patients was high and the prevalence of Anti B2 glycoprotein 1 antibodies and Anti cardiolipin Antibodies were more than FVL.…”
Section: Discussionmentioning
confidence: 63%
“…21.4% of patients had PE without evidence of lower extremities thrombosis. Previous studies showed that deep vein thrombosis (DVT) and superficial vein thrombophlebitis of lower extremities were the typical manifestations, but thrombosis may occur anywhere in the venous system [12,13]. In BD thromboembolism could be rare, maybe due to the high adherence of thrombi to the diseased veins [14].…”
Section: Discussionmentioning
confidence: 99%
“…DVT is believed to result from endothelial inflammation leading to thrombosis through prothrombotic alterations in the vessel wall, upregulation of adhesion molecules and endothelial dysfunction. DVT can occur in any site of the vascular tree, most commonly in lower extremities, but also in hepatic veins, cerebral venous sinuses, superior and inferior vena cava (Ames et al, 2001). Thrombotic events are prevented by ameliorating systemic inflammation, rather than by the institution of primary anticoagulation (Kuzu et al, 1994;Mader et al, 1999;Sarica-Kucukoglu et al, 2006).…”
Section: Venous Thrombosismentioning
confidence: 99%
“…Additionally, cerebral venous thrombosis is a major complication, and cerebral arterial thrombosis is infrequently observed in central nervous system involvement of BD (1)(2)(3). However, embolic stroke with BD has never been reported.…”
Section: Case Reportmentioning
confidence: 99%
“…Patients with BD, especially men, have a significantly high risk of developing systemic venous thrombosis (2,3). In addition, patients with BD may have pulmonary embolism caused by thrombi from venous thrombosis (4).…”
Section: Case Reportmentioning
confidence: 99%